Turkish Foreign Policy in Venezuela: What factors can explain Turkey’s sudden and accelerated rapprochement with Venezuela in the last years? - Karel, Irmak Ekin (2019)
In the last decades, Venezuela became one of the countries in Latin America targeted by Turkey’s new foreign policy towards previously overlooked regions. However, Turkey’s interest in Venezuela mainly remained on paper. It was not until 2016 that Venezuelan-Turkish relations began to flourish at all diplomatic, political and economic levels. Since then, Venezuelan President Nicolás Maduro notably paid four visits to Turkey, whereas Recep Tayyip Erdoğan became the first Turkish President to ever visit Venezuela. Maduro and Erdoğan governments became firm supporters of each other in international politics. Also, the trade volume between both countries in 2018 surpassed the sum of the trade volumes of the previous five years in total. Using the IR theories of realism and constructivism, the paper discusses why Turkey all of a sudden began pursuing an active foreign policy towards Venezuela, a Latin American country that is historically, culturally and geographically distant to Turkey and with which relations were formerly stagnant. It draws the conclusion that the AKP Government under Erdoğan has had both material benefits and ideological support through flourishing relations with the Maduro Government in the last couple of years.